Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1029/2022ja030577
|View full text |Cite
|
Sign up to set email alerts
|

Applying Magnetic Curvature to MMS Data to Identify Thin Current Sheets Relative to Tail Reconnection

Abstract: Thin current sheets (TCSs) have been postulated to be a necessary precondition for reconnection onset. Magnetic reconnection X‐lines in the magnetotail have been observed to be more common duskward of midnight. We take advantage of the MMS tetrahedral formation during the 2017–2020 MMS tail seasons to calculate the thickness of the cross‐tail neutral sheet relative to ion gyroradius. While a similar technique was applied to Cluster data, current sheet thickness over a broader range of radial distances has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…A recent systematic survey of MMS plasma and field data in 2017 (Rogers et al, 2019) identified 12 such magnetotail IDRs, defined as correlated reversals of the proton bulk flow velocity, v x , and the North-South magnetic field, B z , as shown in Figure 1 inset, along with additional Hall magnetic and electric field signatures. That analysis was later extended to 2018-2020 for a total of 26 IDR events (Rogers et al, 2023) labeled here A-Z, "IDR alphabet", listed in Table 2. The second column in the table lists the starting date and time of each IDR interval found in Rogers et al (2023).…”
Section: Reconnection Features In the Equatorial Planementioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic survey of MMS plasma and field data in 2017 (Rogers et al, 2019) identified 12 such magnetotail IDRs, defined as correlated reversals of the proton bulk flow velocity, v x , and the North-South magnetic field, B z , as shown in Figure 1 inset, along with additional Hall magnetic and electric field signatures. That analysis was later extended to 2018-2020 for a total of 26 IDR events (Rogers et al, 2023) labeled here A-Z, "IDR alphabet", listed in Table 2. The second column in the table lists the starting date and time of each IDR interval found in Rogers et al (2023).…”
Section: Reconnection Features In the Equatorial Planementioning
confidence: 99%
“…That analysis was later extended to 2018-2020 for a total of 26 IDR events (Rogers et al, 2023) labeled here A-Z, "IDR alphabet", listed in Table 2. The second column in the table lists the starting date and time of each IDR interval found in Rogers et al (2023). Due to the 5 min cadence of our DM approach, the actual reconstructed times are rounded to the nearest 5 min as indicated in the third column.…”
Section: Reconnection Features In the Equatorial Planementioning
confidence: 99%
See 2 more Smart Citations
“…7 in Tsyganenko (1998)). Thin current sheets are more commonly found from midnight to dusk (Rogers et al., 2023). The anti‐parallel field configuration and low collisionality make it an ideal system to apply the theory.…”
Section: Applicationsmentioning
confidence: 99%